ҚАРАҚАЛПАҚСТАНДАҒЫ АҢЫЗ-ӘПСАНАЛАР МЕНЕН БАЙЛАНЫСЛЫ АЙЫРЫМ ТОПОНИМЛЕР ҲАҚҚЫНДА - Кудиярова, Д. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of toponyms connected with mythology in Karakalpakstan. The materials of the article are important for Linguistics, History and Geography.
Keywords: Onomastics; toponym; etnonym; myth; etymology; history; Linguistics; Geography